O Desenvolvimento socioambiental das praias do município de Caucaia-Ceará: diagnóstico integrado e projeção de cenários - Lira, Claudia Wanderley Pereira de (2015)
Twentieth century development model, based on economic growth oriented the use and occupation of Ceará’s seacoast, caused changes both in land and in the sea zone. Such model attributed capital value to space and this has caused changes in the dynamics of this part of the land as well as in the sea zone. The challenge at present is to avert such alteration by reducing its negative impact and promote development in seacoast. This complex task implies a development model intertwined with economic growth, welfare and providing environment and natural resources preservation for future generations. In order to succeed in that, it is necessary to understand current development dynamics, so, this research aims at analyzing socio-environment development on the beaches of Caucaia City – Ceará: Dois Coqueiros, Iparana, Pacheco, Icaraí, Tabuba, and Cumbuco. The focus is the analysis of their use and occupation between 2000 and 2015; the approach used is geosystemic. The study employs different methodologies such as socio-spatial study from the knowledge of the area under the perspective of analyzed categories; the analysis of plans, projects, laws and instruments; and the integrated analysis from the matrix swot. It is an interdisciplinary study and it covers distinct areas: social, environmental, spatial, and economy. The research also carries out the calculation of the retrograding process of the area through the equation proposed by Brunn Law, used to determinate the preserved area, which is indispensable for seacoast. Information and data were systematized from the correlational matrix and thematic maps, they were presented in scenery forms and the result is some development proposals. The conclusion states that analyzed beaches undergo different processes concerning urban-environmental dynamics; Dois Coqueiros, Iparana, Pacheco and Icaraí beaches need taking their landscape potential back, as well as their socio-economic dynamics; Tabuba and Cumbuco beaches need having their landscape potential and socio-economic dynamics preserved and expanded.